Ethnicity and Race in the UK State of the Nation - Byrne, Bridget (Bristol University Press, 2020)
Available Open Access under CC-BY-NC licence. 50 years after the establishment of the Runnymede Trust and the Race Relations Act of 1968 which sought to end discrimination in public life, this accessible book provides commentary by some of the UK's foremost scholars of race and ethnicity on data relating to a wide range of sectors of society, including employment, health, education, criminal justice, housing and representation in the arts and media. It explores what progress has been made, identifies those areas where inequalities remain stubbornly resistant to change, and asks how our thinking around race and ethnicity has changed in an era of Islamophobia, Brexit and an increasingly diverse population.Available Open Access under CC-BY-NC licence. 50 years after the establishment of the Runnymede Trust and the Race Relations Act of 1968 which sought to end discrimination in public life, this accessible book provides commentary by some of the UK's foremost scholars of race and ethnicity on data relating to a wide range of sectors of society, including employment, health, education, criminal justice, housing and representation in the arts and media. It explores what progress has been made, identifies those areas where inequalities remain stubbornly resistant to change, and asks how our thinking around race and ethnicity has changed in an era of Islamophobia, Brexit and an increasingly diverse population.